(untitled) (Signifiances (Signifying), 2017)
The theory of submorphemic saliencing has tried to show that the notion of « stability » is often expressed in Spanish through words that include the consonantal group st. However, this saliencing is the constitutive marker of the verb estar’s paradigm, generally associated with accidental or circumstantial existence with no essentialising projection, as opposed to the verb ser. Taking a diachronic and synchronic approach based on the signifier, this article aims to explain and understand this apparent contradiction, i.e. the systemic and semantic opposition between ser and estar (sedere/stare). The hypothesis defended in this study is that we are faced with a semantic opposition that can also be seen at the level of the signifiers, which are opposed in two different configurations offering an illustrative example of the motivation of the sign.